Diatom diversity through HTS-metabarcoding in coastal European seas. Issue 1 (December 2018) - Piredda, Roberta; Claverie, Jean-Michel; Decelle, Johan; de Vargas, Colomban; Dunthorn, Micah; Edvardsen, Bente; Eikrem, Wenche; Forster, Dominik; Kooistra, Wiebe; Logares, Ramiro; Massana, Ramon; Montresor, Marina; et al.
Abstract Diatoms constitute a diverse lineage of unicellular organisms abundant and ecologically important in aquatic ecosystems. Compared to other protists, their biology and taxonomy are well-studied, offering the opportunity to combine traditional approaches and new technologies. We examined a dataset of diatom 18S rRNA- and rDNA- (V4 region) reads from different plankton size-fractions and sediments from six European coastal marine sites, with the aim of identifying peculiarities and commonalities with respect to the whole protistan community. Almost all metabarcodes (99.6%) were assigned to known genera (121) and species (236), the most abundant of which were those already known from classic studies and coincided with those seen in light microscopy. rDNA and rRNA showed comparable patterns for the dominant taxa, but rRNA revealed a much higher diversity particularly in the sediment communities. Peculiar to diatoms is a tight bentho-pelagic coupling, with many benthic or planktonic species colonizing both water column and sediments and the dominance of planktonic species in both habitats. Overall metabarcoding results reflected the marked specificity of diatoms compared to other protistan groups in terms of morphological and ecological characteristics, at the same time confirming their great potential in the description of protist communities.